Ecology and management of invasive plants in the sub-Antarctic and Antarctic regions: evidence and synthesis from Macquarie Island. (5th December 2022) - Sindel, Brian M.; Wilson, Susan C.; Wilson, Brian R.; Hawking, Kirsten L.; Zahid, Waqas; Iqbal, Ali; Williams, Laura K.; Knox, Oliver G.G.; Coleman, Michael J.; Kristiansen, Paul
ABSTRACT: Background: The Antarctic is an extreme environment for plants. Several invasive plant species, however, have invaded the sub-Antarctic Southern Ocean islands and increasingly threaten the vulnerability of maritime and continental Antarctica, particularly with changes in climate. Aims: We provide an overview of issues to consider with regard to the impact, ecology and management of non-native plants in the Antarctic, focusing on knowledge gained and recent research results from the sub-Antarctic with possible application to Antarctica. Methods: We provide a brief review of literature and bring together experience and previously unpublished research with Poa annua and Stellaria media on Macquarie Island. Results: While no one set of biological characteristics predicts plant invasiveness in the sub-Antarctic, all are adapted to survive extreme cold conditions and persistence is enabled through large and long-lived soil seed banks. Ecological drivers for invasion include accidental human introductions and continuing movement, along with animal and other disturbance to soil. Conclusion: The invasive cold-tolerant plant species now prevalent on sub-Antarctic islands also pose a threat to Antarctica due to a warming climate and so efforts should continue to prevent further spread, while developing effective, low-impact control and eradication options to protect these high-value extreme ecosystems.